The impact of merchandise assortment on customer retention: a case study of Village Spar - Sikwila, Nyasha (2018)
The study was based on the impact of merchandise assortment on customer retention, the case study being Village Spar. The researcher was inspired to carry out a study on this topic, because she saw firsthand the benefits that lay with good merchandising strategies. However environmental influences have since seen the Village Spar facing challenges that have affected assortment size. Statement of the problem is given. The objectives that were governing the study were, to find out the importance of product assortment within a product line, to determine the influence of a brand name on purchasing decisions within a merchandise mix, to establish the importance of shelf space in retailing and to find out the importance of customer profile on product assortment. Like any other project, not all aspects will be in the control of the researcher. Time, finances and information conveyed pose as limitations. In order to achieve the stated objectives the researcher sought out the views of numerous authors so as to understand product assortment, the link between brand name and merchandise mix, shelf space and influence of customer profile on the store offering. An in depth review of literature from various authors was carried out. It was discussion oriented, thus giving a balanced point of view since authors that supported the notion and those that opposed were all meshed in one chapter. The researcher utilized both explorative and descriptive research to obtain both qualitative and quantitative data surrounding the problem in question. The research instruments that were employed were questionnaires and an interview. Haphazard sampling was used as a sampling method since respondents were selected based on ease and convenience. The sample elements consisted of 14 merchandisers, 1 manager and 30 customers who responded. In assistance was secondary and primary data as sources of data. The findings from the respondents were analyzed, described and presented using graphs, tables and pie charts. The response rate was 86%, which was translated as the results found being reliable. In conclusion based on the study and literature, assortment size has an impact on customer retention. This was supported by 87% of the customers who participated in the study were in agreement that they considered the stores assortment size before they patronized it. The study recommended that Village Spar carries’ out a gaps analysis on its assortment on a regular bases at the same time being abreast with the ever changing global environment, consumer tastes and preference. Also being assortment intelligent through the use of information systems software which helps manage assortment. Through customer profiling the retailer can maximizing on building customer relations which assist in designing the assortment. A brands name defines the quality, price and the type of customer who will buy that product. Brand name is one aspect the retailer has to consider when defining his or hers assortment offering as it assists the customer in recalling and identification of the product. In as much as the retailer may want to carry large assortments, shelf space is one aspect in retailing that can be a limiting factor. In light of this careful shelf space allocation should be done. Areas for further study such as customer relationship were suggested as drivers of retention.